Comparative Studies of the Phytochemical Analysis, Mineral Content, Antibacterial Activity and Antioxidant Potential of Ethyl Acetate Extract of Alstonia Boonei Leaves and Stem Bark - Uadia, Jeremiah Ogboma; Ogbeide, Osahon Kennedy (Department of Chemistry Faculty of Science and Technology Walisongo, 2024)
Folkloric medicine has reported the effectiveness of Alstonia boonei stem bark and leaf extracts in treating and managing different ailments. Hence, this research is a comparative evaluation of the phytochemicals; antioxidant potential, mineral content, and antibacterial capacity of ethyl acetate extract of Alstonia boonei leaves and stem bark. Phytochemical analysis was determined using standard methods; mineral composition was determined using a flame photometer and an atomic absorption spectrophotometer; antibacterial capacity was analysed by agar-well diffusion method; and antioxidant potential was examined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method. The phytochemicals detected were phenolics, eugenols, steroids, flavonoids, alkaloids, and reducing sugars in both extracts. Mineral content for sodium, iron, potassium, zinc, copper, magnesium and calcium was found to be 5.61 ± 1.33, 7.25 ± 1.00, 120.63 ± 1.39, 1.62 ± 0.30, 1.01 ± 0.01, 2.36 ± 0.10 and 15.61 ± 1.20 mg/kg respectively for the leaf extract, and 9.36 ± 0.35, 6.36 ± 0.55, 113.64 ± 0.45, 2.40 ± 0.32, 0.02 ± 0.00, 2.10 ± 0.50 and 28.30 ± 0.22 mg/kg respectively for the stem bark extract. The antioxidant potential at 250, 200, 150, 100, and 50 g/mL gave an IC50 of 2.89 ± 0.51, 3.90 ± 0.50, and 2.52 ± 0.22 μg/mL for leaf extract, stem bark extract and standard, respectively. The minimum inhibitory concentration (MIC) outcome was identical for both extracts except for P. aeruginosa. Both extracts' minimum bactericidal concentration (MBC) values were 12.5 to 50 mg/mL, except B. subtilis. Hence, this result provides valuable insight into the comparative usefulness of the plant in phytomedicine.